Up and Down the Geographical and Temporal Scales: Integrating Global Trends and Local Decisions to Make the World More Food-Secure in 2050 - Rosegrant, Mark W.; Perez, Nicostrato; Pradesha, Angga; Thomas, Timothy S.; Sombilla, Mercedita A. (2015)
Presentation by Mark W. Rosegrant, Nicostrato Perez, Angga Pradesha, Timothy S. Thomas, and Mercedita A. Sombilla at the Global Landscapes Forum on December 5, 2015 in Paris, France